2023
DOI: 10.1126/sciadv.adg7676
|View full text |Cite
|
Sign up to set email alerts
|

Alternative epidemic indicators for COVID-19 in three settings with incomplete death registration systems

Abstract: Not all COVID-19 deaths are officially reported, and particularly in low-income and humanitarian settings, the magnitude of reporting gaps remains sparsely characterized. Alternative data sources, including burial site worker reports, satellite imagery of cemeteries, and social media–conducted surveys of infection may offer solutions. By merging these data with independently conducted, representative serological studies within a mathematical modeling framework, we aim to better understand the range of underrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…IFRs for other African countries, including Ethiopia, Mozambique, and South Africa, exceeded 0.5 percent, well above population benchmarks for high-income countries from other studies using the same methodology (Levin et al 2020). Additionally, recent work focusing on the highly characterized epidemic in Lusaka, Zambia, and conducted to match the IFR study by Brazeau et al (2022), found that the impact of the first pandemic wave in Lusaka during 2020 was highly consistent with COVID-19 epidemics elsewhere, leaving little room for any so-called "Africa paradox" (Sheppard et al 2023).…”
Section: Covid-19 Mortality In African Countriesmentioning
confidence: 73%
See 2 more Smart Citations
“…IFRs for other African countries, including Ethiopia, Mozambique, and South Africa, exceeded 0.5 percent, well above population benchmarks for high-income countries from other studies using the same methodology (Levin et al 2020). Additionally, recent work focusing on the highly characterized epidemic in Lusaka, Zambia, and conducted to match the IFR study by Brazeau et al (2022), found that the impact of the first pandemic wave in Lusaka during 2020 was highly consistent with COVID-19 epidemics elsewhere, leaving little room for any so-called "Africa paradox" (Sheppard et al 2023).…”
Section: Covid-19 Mortality In African Countriesmentioning
confidence: 73%
“…Observed death was significantly higher in the third quarter of 2020 for ages 35-49, 50-64, and 65+ and for both men and women. Additional work bringing together data from burial site worker reports, satellite imagery of cemeteries, social media-conducted surveys of infection, and representative serological studies from three major cities-Addis Ababa (Ethiopia), Aden (Yemen), and Khartoum (Sudan)-during 2020, researchers show substantial impacts of the pandemic coupled with high variability across contexts in the percentage of COVID-19 deaths that were reported (McCabe et al 2023). In Aden, Yemen, satellite imagery surveillance of all cemeteries from July 2016 to September 2020 suggests that an additional 2,120 excess deaths occurred from April 1, 2020, to September 19, 2020.…”
Section: Critiques and Responsesmentioning
confidence: 99%
See 1 more Smart Citation